Fractals on IPv6 Network Topology - Jun Zhang; Hai Zhao; Bo Yang; Si-yuan Jia (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The coarse-grained renormalization and the fractal analysis of the Internet macroscopic topology can help people better understand the relationship between the part and whole of the Internet, and it is significant for people to understand the essence of the research object through a small amount of information. Aiming at the complexity of Internet IPv6 IP-level topology, we put forward a method of core-threshold coarse-grained to renormalize its topology. By analyzing the degree distribution and degree correlation characteristics in each k-core network topology, the scale invariance of the networks of coarse-grained renormalization was illustrated. The fractal dimension of Internet IPv6 IP-level topology was further computed which shows that the Internet IPv6 IP-level topology has got fractals. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.1979